2015
DOI: 10.1186/s12865-014-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of dehydroepiandrosterone as a potential mechanism of dendritic cell impairment during pregnancy

Abstract: BackgroundThis study aimed to test the hypothesis that immune dysfunction and the increased risk of spontaneous abortion in pregnant women with hyperandrogenia (HA) are caused by the reduced tolerogenic potential of dendritic cells (DCs) that results from elevated levels of dehydroepiandrosterone sulfate (DHEAS).MethodsThe phenotypic and functional properties of monocyte-derived DCs generated from blood monocytes from non-pregnant women, women with a normal pregnancy, or pregnant women with HA, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…hASC and PBMC were isolated from fat tissue and venous blood of healthy donors ( n = 6 and n = 4, resp.). Donor hASC were cultured with activated T cells, which were isolated as a part of donor PBMC preparation (PBMC typically contain approximately 70% of T cells) [ 30 ]. To activate T cells, we used either phytohemagglutinin (PHA) or plate-bound anti-CD3 and anti-CD28 antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…hASC and PBMC were isolated from fat tissue and venous blood of healthy donors ( n = 6 and n = 4, resp.). Donor hASC were cultured with activated T cells, which were isolated as a part of donor PBMC preparation (PBMC typically contain approximately 70% of T cells) [ 30 ]. To activate T cells, we used either phytohemagglutinin (PHA) or plate-bound anti-CD3 and anti-CD28 antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Chernykh et al . showed that DC impairment was found in patients with elevated DHEAS 58 . High levels of DHEAS could cause spontaneous abortions by causing abnormal immunization in pregnant women.…”
Section: Discussionmentioning
confidence: 95%
“…CD274, as a B7 family member, plays an important role in inducing T cell activation and differentiation. Previous study showed that DCs from a normal pregnancy peripheral expressed a high level of CD274 compared to DCs in unpregnant women [ 31 ]. Our study further proved that DCs from RSA patients and RSA mice were characterized by decreased expression of CD274 compared with the NP group, which might contribute to an abnormal T cell activation and differentiation.…”
Section: Discussionmentioning
confidence: 99%